Improving participants’ recruitment in dementia-related studies on social media through colloquial language in Lima, Peru - Belén Custodio; Maria Mora-Pinzon; Rosa Montesinos; Maria Eugenia Godoy; José Carlos Huilca; Katherine Agüero; Nilton Custodio (Dementia & Neuropsychologia)
ABSTRACT Recruitment for dementia research remains a persistent challenge, particularly when trying to reach underrepresented groups such as Latin Americans with traditional enrollment strategies. Objective: In this retrospective case study, we investigate two communication approaches used on social media to recruit participants for a dementia research study in Lima, Peru. Methods: Initially, recruitment materials featured medical terminology, which was later replaced by colloquial language to make the content more accessible. Results: According to the results, using simpler and more relatable language led to an increase in participants’ contacts and enrollments. This suggests that culturally tailored communication strategies may be more effective in reaching diverse populations. Conclusion: The findings highlight the importance of adapting research recruitment efforts to the target community’s cultural and linguistic context to improve engagement in dementia studies.